Tasks and Rubrics for Assessing Research Skills of Undergraduate Students - Nasrudin, Dindin; Dirgantara, Yudi; Suhendi, Herni Yuniarti (Institut Agama Islam Negeri Sorong, 2022)
Intraarticular learning can improve students' research skills, one of which is strengthening educational seminar courses. This research aims to develop a task and rubric to assess undergraduate students' research skills. This study is a research and development using the DDD-E model design (Decide, Design, Development, and Evaluation). This research has succeeded in compiling a task and rubric to measure undergraduate students' research skills in preparing research proposals. This rubric can be implemented by researchers in the broader area with some adjustments.